Working conditions of a nursing team in mental health facility - Aline Silvia Esteves Morais; Gisele Fernandes Tarma Cordeiro; Angela Aparecida Peters; Tatiana Marques dos Santos; Rosa Gomes dos Santos Ferreira; Maria Angélica de Almeida Peres
ABSTRACT Objective: To analyze how the nursing team from a Psychosocial Care Center II relates its insertion in the service with the work process. Methods: Descriptive, analytical research outlined as a case study with a qualitative approach. The data were collected through semi-structured interviews with nursing professionals and went through content analysis subsidized by Bardin's work. Results: Two thematic categories emerged: a) Ways of intake in the nursing services at the Psychosocial Care Center; b) Setbacks in nursing routine at the Psychosocial Care Center. Final considerations: The fact that the professionals have not planned to work in mental health nor have training impacts the rhythm of psychosocial care development at the Psychosocial Care Center, forcing them to seek training in the field after admission. Unmotivated by the working conditions, the nursing team suffers from the absence of an interdisciplinary partnership and goes to great lengths to approach psychosocial care.